2022
DOI: 10.24928/2022/0207
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Quality Performance Outcomes and the Relationship With Staffing: A General Contractor Case Study

Abstract: This paper describes a methodology for understanding how staffing projects may be assessed and considers how it may relate to project team performance when project teams implement a Systems Approach to Quality (SAQ). This paper expands on the 2021 paper "The Impact of Implementing a System Approach to Quality: A General Contractor Case Study" where the authors compared project performance outcomes and team cultural assessments for 11 projects that had implemented SAQ, the Intervention group, to a similar set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The median value for the Intervention group was .09% and 19% for the Control group" (Gordon et al, 2022). The median value for time coded to VDC resources was approximately 3x more for the Intervention projects (Gordon et al, 2022).…”
Section: Previous Researchmentioning
confidence: 96%
See 2 more Smart Citations
“…The median value for the Intervention group was .09% and 19% for the Control group" (Gordon et al, 2022). The median value for time coded to VDC resources was approximately 3x more for the Intervention projects (Gordon et al, 2022).…”
Section: Previous Researchmentioning
confidence: 96%
“…The first paper measured project performance outcomes between the two groups for cost, schedule, change management, safety, quality, and cultural outcomes using Quinn's Competing Values Framework (CVF) and found that those that implemented SAQ had better performance outcomes more aligned with company objectives (Gordon et al 2021a). In follow-up research, Gordon et al, 2022 reviewed contract date relative to project duration and studied staffing and resourcing profiles between the project groups to understand if different inputs contributed to better performance outcomes (Gordon et al 2022).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed and thorough communication channels play a pivotal role in understanding the definition of quality requirements, integrating them into the project design, and measuring them. This process sometimes requires tools like product samples, mockups, or virtual reality for stakeholders to experience the project in real time (Gordon, 2023). Problem Solving Symptoms gap: The construction industry tends to prioritize treating symptoms over uncovering root causes (Abdelhamid, & Everett, 2000), posing challenges in identifying the actual problems within its complex network.…”
Section: Gaps To Trust In Constructionmentioning
confidence: 99%
“…Knowing that others rely on our performance motivates us to complete tasks as promised, maintaining the expected quality level for the subsequent parties involved (Scarnati, 2001). Quality Before Construction: Teams must practice design quality of installation into the design of the product before the product is ready to be built (Gordon, 2023). There are two forms of expectations when it comes to the quality of products delivered in construction.…”
Section: Trust As a Solutionmentioning
confidence: 99%